Decision Making among Women: Headed Households - K. Uma Rani,; K. Sai Maheswari,; G. Bhaskar, (Journal of Agricultural Extension Management, 2025)
Agriculture is a family enterprise in which both men and women play different roles and undertake different activities, which are complementary to each other. Women, particularly belonging to small and marginal households, play roles such as decision maker, supervisor, member of the family work force, agricultural labourer and sometimes as a head of the farm and home. Among farm women there exists a separate category, that is, women who head households either out of compulsion or by choice. Farm women who head the households are mostly the widows, or spouse of the migrant husband who left the farm in search of better livelihood, sick and disabled husband etc. Such households are a separate category and cannot be equated with other households. The burden of heading the family by a woman has a double-edged problem of home and farm management. In managing the home, she makes many decisions for the welfare of the family members, including herself. Similarly, in economic pursuits, the farm becomes the main source of livelihood around which all farm-related decisions are involved. Thus, the role of the woman in the family she is heading, is dual in nature and the problems multiply in case of poor women with few or no resources excepting the sale of labour